Growth kinetic of rhizopus sp. immobilised on loofah sponge for whole-cell biocatalyst in different cultivation media / Azlin Suhaida Azmi … [et al.] - Azmi, Azlin Suhaida; Mohd Bakari, Nur Atikah; Ali, Fathilah; Mohamad Puad, Noor Illi; Ahmad, Farah (Universiti Teknologi MARA, 2022)
Immobilisation of filamentous fungi such as Rhizopus sp. onto biomass support particles (BSP) surface was studied as whole-cell biocatalyst. The function was to aid fermentation process. By using the microbial immobilisation process, the complex procedures of isolation, purification and immobilisation of extracellular enzyme can be avoided. Loofa sponge was selected as the BSP to aid in the immobilisation of the cells. In this study, the growth of immobilised Rhizopus sp. on loofa sponge was compared in four different cultivation media and the attachment of Rhizopus sp. on loofa sponge was investigated using scanning electron microscopy (SEM). The media used in this study were hydrolysed cassava starch, cassava dextrose, potato dextrose, and soy dextrose. The process condition and other parameters which were temperature, pH, inoculum dilution, and weight of loofa sponge, fixed at 30 °C, 7, 20 mL, and 2 g, respectively. The highest and lowest of maximum growth (ymax) of the immobilised cells were determined from potato dextrose and soy powder mixed with dextrose media, respectively at 1.5281 g/g and 1.0370 g/g. Whilst, the highest and lowest observed rate constant (k) were obtained from cassava starch mixed with dextrose and soy powder mixed with dextrose, which respectively at 2.9403 day−1 and −0.8763 day−1. SEM images showed the presence of mycelia attached to the loofah sponge after immobilisation process. In conclusion, Rhizopus sp. has been successfully immobilised on loofah sponge as a whole-cell biocatalyst.